160k views
3 votes
Hi. I need help with this questions.
See image for question



Hi. I need help with this questions. See image for question ​-example-1

1 Answer

4 votes

Answer:

  • None

Explanation:

Given expression

  • 9x² - 2(k + 7)x + k

If this is a perfect square then it should be in the form of:

  • (3x)² - 2(3x)(√k) + (√k)²

Comparing the two expressions, we see that:

  • (k + 7) = 3√k
  • (k + 7)² = 9k
  • k² + 14k + 49 - 9k = 0
  • k² + 5k + 49 = 0
  • D = √(5² -4*49) = √-171

Since the discriminant is negative, there is no solution

User Chester
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.